The Evolution of Human Rights in the United States: From the 1787 Constitution to the Modern Era - Alexandra M. Harper (JOCER: Journal of Civic Education Research, 2025)
This study examines the historical evolution of human rights in the United States, focusing on the specific question of how key constitutional and legal developments from the 1787 Constitution to the modern era have shaped the nation’s human rights framework.. Employing a qualitative historical methodology, this research applies systematic document analysis including predefined inclusion criteria, source triangulation, and thematic coding on constitutional texts, Supreme Court rulings, official government documents, and relevant scholarly literature to ensure methodological rigor and analytical consistency. The findings reveal a non-linear evolution of human rights in the U.S., demonstrated through specific cases such as the Bill of Rights amendments, key Supreme Court decisions including Brown v. Board of Education and Roe v. Wade, and shifting federal–state dynamics that highlight persistent tensions between constitutional ideals and socio-political realities.. Early constitutional provisions embedded liberty and equality as principles, yet their practical application often excluded marginalized groups, particularly racial minorities, Indigenous peoples, and women. Significant advancements, such as those during the Reconstruction era and the Civil Rights Movement, demonstrate that human rights progress results from the intersection of social mobilization, political pressures, and judicial reinterpretation. In the modern context, the scope of human rights has expanded to encompass issues of gender, sexual identity, minority protections, and critiques of structural inequality, although resistance from traditionalist or conservative actors persists. This study underscores that human rights in the United States evolve through continuous dialectics between law, politics, and society, rather than solely through legal reform. The research contributes to scholarly understanding by highlighting the complex interplay of historical, social, and institutional factors shaping the trajectory of human rights and by filling gaps in the literature concerning the longitudinal analysis of constitutional and social dynamics.